Different nitrogen sources speed recovery from corallivory and uniquely alter the microbiome of a reef-building coral - Mallory M. Rice; Rebecca L. Maher; Rebecca Vega Thurber; Deron E. Burkepile (PeerJ, 2019)
Corals are in decline worldwide due to local anthropogenic stressors, such as nutrient loading, and global stressors, such as ocean warming. Anthropogenic nutrient loading, which is often rich in nitrate, inhibits coral growth and worsens corals’ response to warming while natural sources of nitrogen, such as ammonium from fish excretion, promotes coral growth. Although the effects of nutrient loading and ocean warming have been well-studied, it remains unclear how these factors may interact with biotic processes, such as corallivory, to alter coral health and the coral microbiome. This study examined how nitrate vs. ammonium enrichment altered the effects of increased seawater temperature and simulated parrotfish corallivory on the health of Pocillopora meandrina and its microbial community. We tested the effects of nitrogen source on the response to corallivory under contrasting temperatures (control: 26 °C, warming: 29 °C) in a factorial mesocosm experiment in Moorea, French Polynesia. Corals were able to maintain growth rates despite simultaneous stressors. Seawater warming suppressed wound healing rates by nearly 66%. However, both ammonium and nitrate enrichment counteracted the effect of higher temperatures on would healing rates. Elevated seawater temperature and ammonium enrichment independently increased Symbiodiniaceae densities relative to controls, yet there was no effect of nitrate enrichment on algal symbiont densities. Microbiome variability increased with the addition of nitrate or ammonium. Moreover, microbial indicator analysis showed that Desulfovibrionaceae Operational taxonomic units (OTUs) are indicators of exclusively temperature stress while Rhodobacteraceae and Saprospiraceae OTUs were indicators of high temperature, wounding, and nitrogen enrichment. Overall, our results suggest that nitrogen source may not alter the response of the coral host to simultaneous stressors, but that the associated microbial community may be distinct depending on the source of enrichment.